2004
DOI: 10.1111/j.1467-8624.2004.00688.x
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Maternal Characteristics and Contextual Variables on Infant–Mother Attachment

Abstract: This prospective study examined the effects of maternal characteristics, social support, and risk factors on infant-mother attachment in a heterogeneous sample. Two hundred and six women between the ages of 18 and 40 were interviewed during their last trimester of pregnancy and 1 year postpartum. Structural equation modeling revealed that maternal attachment experiences were significantly related to prenatal representations of the infant and of the self as a mother, which were significantly related to infant-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
111
2
8

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 160 publications
(136 citation statements)
references
References 65 publications
7
111
2
8
Order By: Relevance
“…Please see Huth-Bocks (Huth Bocks, Levendosky, Bogat, & Von Eye, 2004), for a more complete description of the recruitment procedures.…”
Section: Recruitmentmentioning
confidence: 99%
“…Please see Huth-Bocks (Huth Bocks, Levendosky, Bogat, & Von Eye, 2004), for a more complete description of the recruitment procedures.…”
Section: Recruitmentmentioning
confidence: 99%
“…Factors that can present as a risk to this early relationship are maternal depression 26 , lack of parental social support 27 , bereavement 28 and infant temperament 29 . Although there has been an assumption that parents find it harder to bond with a baby with a facial disfigurement 30,31 , there is growing evidence that babies born with a cleft are not at particular risk of developing an insecure attachment 32,33 .…”
Section: Nurturing the Parents Of A Newborn With A Cleftmentioning
confidence: 99%
“…The results showed that mothers in the intervention group, who exercised more frequently and talked to the fetus every day in Gestational Weeks 34 and 36, had a higher level of maternal-fetal attachment. According to earlier studies, increasing the frequency of talking to the fetus every day is another approach to increasing fetal attachment [36][37][38]. However, one study observed no difference in the level of maternal-fetal attachment for women with and without intervention regardless of the frequency of talking to the fetus in Gestational Week 30, because the gestational age was a strong predictor of maternal-fetal attachment [39].…”
Section: Related Intervention Studies On Maternal-fetal Attachmentmentioning
confidence: 99%